Transformation of the Muslim Women's Da'wah Movement Facing the Global Issue of Feminism Movement - Suhartini Ashari (Yayasan Adra Karima Hubbi, 2025)
Feminism was born out of women's dissatisfaction with men's oppressive attitudes and marginalizing their roles. They demand equality of treatment, demand recognition of their role in family life, and even more so in various sectors of community life. Feminism, which was originally sectoral in nature, has become a movement and globalized to all corners of the world, including the Islamic world. Information technology has a bearing on the spread of feminism issues throughout the world so as to influence the mindset of society, including Islamic society. Feminist struggles in many cases contradict Islamic values. The task of Islamic da'wah in this case is to straighten out their thinking. Muslim da'wah is the most appropriate da'wah element to answer the issues of feminism. The issue of feminism and the role of Muslim da'wah in countering feminism raises at least two questions, namely how feminism and their struggle actually became a global movement and how Muslim da'wah answers the global challenges of the feminism movement. To answer these questions, researchers used a qualitative research method using a literature approach. Data analysis is focused on the transformation of Muslim da'wah in facing the global issue of feminism movement. The result is that the issue of feminism spreads throughout the world including the Islamic world following the development of modernization and information technology. In response to this, Muslim da'wah must be able to transform by using information technology as a manifestation of da'wah bil hikmah. The development of da'wah methods today favors the use of audio visuals on digital and online media. The use of audio visual media can be done by combining the methods of bil lisan, bil qalam and bil hal.